2012
DOI: 10.1007/s10616-012-9452-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of leptin gene expression and secretion by silibinin: possible role of estrogen receptors

Abstract: Leptin plays the role of mitogenic factor in the breast carcinogenesis. Therefore, it could be considered as a target for breast cancer therapy. Leptin gene expression could be modulated by activation of estrogen receptors. Silibinin is an herbal compound with anti-cancer activity on prostate and colorectal cancers. Based on the fact that targeting of leptin can be considered as a novel strategy for breast cancer therapy, the aim of this study was the investigation of potentiality of silibinin for inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Thus, it seems that curcumin and silibinin intensify each other's inhibitory effects on leptin and its receptor genes expression and this intensifying effect may be through similar mechanisms. The mechanism for declining the expression of leptin was proposed by a recent study (Nejati-Koshki et al, 2012). This study showed that silibinin can decrease the expression of leptin in T47D cell line through increasing of ERβ/ERα (estrogen receptor β/ estrogen receptor α) gene expression ratio.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, it seems that curcumin and silibinin intensify each other's inhibitory effects on leptin and its receptor genes expression and this intensifying effect may be through similar mechanisms. The mechanism for declining the expression of leptin was proposed by a recent study (Nejati-Koshki et al, 2012). This study showed that silibinin can decrease the expression of leptin in T47D cell line through increasing of ERβ/ERα (estrogen receptor β/ estrogen receptor α) gene expression ratio.…”
Section: Discussionmentioning
confidence: 84%
“…Also, another study demonstrated the inhibitory effect of curcumin on expression of ERα, and thus, the increasing of ERβ/ERα gene expression ratio (Boominathan and Lakshmanane, 2009). Therefore, based on the results of these two studies (Boominathan and Lakshmanane, 2009;Nejati-Koshki et al, 2012), the decrease in the leptin gene expression by curcumin can be done through the decreasing in the ERα gene expression (increasing in the ERβ/ERα expression ratio).…”
Section: Discussionmentioning
confidence: 93%
“…Leptin produced by adjacent adipose might provide a local increased level of stimulation to tumors 6062 , suggesting the presence of tumor associated adipose represents an important microenvironmental influence. Although normally secreted from adipose, self-sufficiency for leptin has recently been shown to be secreted from glioblastoma and breast cancer cells 63, 64 . Further, intra-tumoral mRNA leptin levels in patients with high leptin receptor levels correlated with decreased relapse-free survival 55 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, leptin and its receptor can serve as targets for designing targeted anti-breast cancer drugs. It inhibits leptin gene expression and secretion in T47D breast cancer cells in a time and dose dependent manner [95]. More compounds that can inhibit leptin receptor signaling to kill leptin receptorpositive cancer cells have been discovered in another patent [94].…”
Section: Drugs Designed To Target Other Breast Cancer Markersmentioning
confidence: 99%
“…Therefore, more efforts are needed to advance breast cancer treatment by developing more innovative therapies. These observations suggested that MSCs can function as a novel vehicle for [139,140] Trastuzumab HER2 receptor [11,12] siRNA target HER2 HER2 fragment [15] 4D5 of HER2 antibody Epitope 4D5 of HER2 [17] Tamoxifen Estrogen receptor [21] Polymer: tamoxifen Estrogen receptor [22] Fulvestrant Estrogen receptor [23][24][25] Bevacizumab VEGF [56,59] Anti-annexin II antibodies Anti-angiogenesis [75] siRNA target Protein kinase C Protein kinase C [84,86] Anti-HER3 antibodies HER3 [90] Anti-158P3D2 158P3D2 [99] Leptin VEGF [92,95] Recombinant MSC:IL-12 Metastatic breast cancer [110] NSC: Trastuzumab Metastatic breast cancer [119] NSC: Carboxylesterase Metastatic breast cancer [121] HER2 aptamers HER2 [127,129] -Fetoprotein Breast cancer growth [133][134][135][136] Polymer: Trastuzumab HER2 [143] Polymer: Trastuzumab & docetaxel HER2 and tumor growth [145] Nanoparticle: Tamoxifen Tumor growth [146] delivering therapeutic agents into breast cancer tumors. Based on these discoveries, they developed a method for targeting the cellular interactions between MSCs and breast cancer cells, making cancer cells more susceptible to chemotherapy.…”
Section: Current and Future Developmentsmentioning
confidence: 99%